Adán Buenosayres: an Argentinian Ulysses - Davis González, Ana (Romanica Olomucensia, 2017)
The first part of the study offers various perspectives on the connection between Marechal's novel Adan Buenosayres (1948) and Joyce's Ulysses (1922). The difference between those who consider it plagiarism and those who see an emulation of Ulysses in Adam shows how complex the comparison of texts can be. The second part of the research offers, in a synthetic way, the most relevant theoretical issues about intertextuality and focuses on the readings of Joyce's novel that Marechal carried out. The work closes by revealing formal aspects and content that both works share, which have not yet been developed in detail. The final conclusion proposes that Adan and Ulysses fulfil the same function within the literary field of their countries of origin.
Keywords: Leopoldo Marechal; Adán Buenosayres; Ulises; James Joyce; intertextuality